2018
DOI: 10.1007/s11060-018-03037-3
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of neuropathological diagnoses in patients undergoing surgery for suspected recurrence of glioblastoma

Abstract: PurposeClinical factors and neuro-imaging in patients with glioblastoma who appear to progress following standard chemoradiation are unable to reliably distinguish tumor progression from pseudo-progression. As a result, surgery is commonly recommended to establish a final diagnosis. However, studies evaluating the pathologists’ agreement on pathologic diagnoses in this setting have not been previously evaluated.MethodsA hypothetical clinical history coupled with images of histological sections from 13 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For example, although pathological diagnosis is considered the gold standard, it provides molecular characterization of the glioma at a single snapshot in time (e.g., prior to chemoradiation, or in the case of recurrent disease, after multiple treatments including chemoradiation) and is limited in scope to the tumor region sampled by neurosurgeon. In addition, multiple reports have demonstrated inter-rater variability for glioma pathology diagnosis among trained experts, and the superiority of molecular and genetic profiles compared to histological analyses for prediction of overall survival (OS) in patients with glioma (3,4). Instead, by implementing an advanced MI-based approach, the molecular marker status of tumors could be interrogated repeatedly in vivo over the course of the patient's treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although pathological diagnosis is considered the gold standard, it provides molecular characterization of the glioma at a single snapshot in time (e.g., prior to chemoradiation, or in the case of recurrent disease, after multiple treatments including chemoradiation) and is limited in scope to the tumor region sampled by neurosurgeon. In addition, multiple reports have demonstrated inter-rater variability for glioma pathology diagnosis among trained experts, and the superiority of molecular and genetic profiles compared to histological analyses for prediction of overall survival (OS) in patients with glioma (3,4). Instead, by implementing an advanced MI-based approach, the molecular marker status of tumors could be interrogated repeatedly in vivo over the course of the patient's treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Because glioblastomas are markedly heterogeneous tumors, histopathologic diagnosis of samples from separate locations may differ; even with a given sample, diagnostic agreement among pathologists can vary. 24 However, despite the real possibility of sampling error, histopathologic assessment remains the "criterion standard" for determining disease status and often influences treatment-related decision-making. Taking these issues into consideration, we show the potential of FTB to distinguish TE from tumor, and we have yet to fully explore its role as an alternative means to provide accurate diagnostic and prognostic information, particularly given the limitations of histopathologic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly emphasized by the study conducted by Holdhoff, et al, in which only "marginal agreement" by Fleiss' kappa statistics was observed when 48 pathologists (92% of whom were neuropathologists) reviewed 13 cases of suspected recurrence of glioblastoma. [14] Much of this may be due to differential understanding of the terminology used in this this study. The terminology of "active tumor", "inactive tumor", and "treatment effect" are not well established in the literature [14] yet this is commonly used terminology.…”
Section: Summary and Commentary On Previously Published Neuropathology Guidelinementioning
confidence: 99%